Improvement of Power Electronic Structure Characteristics Using Sic Technology - Overview - Dobrucky, Branislav; Spanik, Pavol; Sul, Robert (Communications - Scientific letters of the University of Zilina, 2006)
This paper is dedicated to the recent unprecedented boom of SiC electronic technology. The contribution deals with a brief survey of those properties. In particular, the differences (both good and bad) between SiC electronics technology and well-known silicon VLSI technology are highlighted. Projected performance benefits of SiC electronics are given for several large-scale applications at the end of the contribution. The basic properties of SiC material were discussed already at the beginning of 1980’s, also in our work place [1].